MODEL DAN EFEK DUKUNGAN SOSIAL TERHADAP KEPATUHAN PENGOBATAN PASIEN TUBERKULOSIS RESISTEN OBAT : A LITERATURE REVIEW - Sudirman Efendi; Elly Lilianty Sjattar; Yuliana Syam (Universitas Islam Negeri Alauddin Makassar, 2021)
Introduction:Tuberculosis is an infectious disease that often ends in death. Poor adherence is a major threat to control and encourages the emergence of drug-resistant TB. Drug-resistant TB patients are synonymous with psychosocial problems such as stigma and psychological distress that impact adherence and treatment outcomes. Social support is the key to treatment adherence which includes emotional, informational, economic support and patient assistance during treatment. Purpose: This study aims to identify and describe the model and effect of social support on treatment adherence in drug-resistant TB patients.Methods: P A literature review search was performed using the PICO keyword in four article databases, namely PubMed, Science Direct, ProQuest Cochrane Library and Gray literature. reported in English over the past six years on social support and drug-resistant TB. Results: Based on the 6 articles reviewed, several were identified models or forms of social support interventions given to TB-resistant patients and has a positive impact on medication adherence . In addition, it also has an impact on increasing knowledge, reducing stigma and psychological problems which helps the patient's healing process.Conclusion:Social support has a positive impact on treatment adherence so it is recommended to be applied in treatment programs for drug-resistant TB patients.Keywords: drug resisten tuberculosis ; social support ; treatment obedience